Gamification Approach and Students' Motivation in Learning English: A Literature Review - Neman, Meily Ivane Esther (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Klabat, 2024)
This literature review examines how the influence of gamification on student motivation in the context of learning English. The study examines 18 research that investigates the impact of gamification components, such as points, badges, leaderboards, stories, and competition, on student engagement and motivation. The findings strongly support the beneficial impacts of gamification. Research indicates that it promotes a more pleasurable and engaging learning encounter, resulting in heightened student motivation. Gamification can boost both intrinsic and extrinsic motivation. In general, gamification is seen as an effective method for increasing student motivation and creating a more captivating learning environment for ESL and EFL learners.